Variation of Oxygenation Conditions on a Hydrocarbonoclastic Microbial Community Reveals Alcanivorax and Cycloclasticus Ecotypes - Terrisse, Fanny; Cravo-Laureau, Cristiana; Noël, Cyril; Cagnon, Christine; Dumbrell, Alex J.; McGenity, Terry J.; Duran, Robert (Frontiers in Microbiology, 2017)
Deciphering the ecology of marine obligate hydrocarbonoclastic bacteria (MOHCB) is of crucial importance for understanding their success in occupying distinct niches in hydrocarbon-contaminated marine environments after oil spills. In marine coastal sediments, MOHCB are particularly subjected to extreme fluctuating conditions due to redox oscillations several times a day as a result of mechanical (tide, waves and currents) and biological (bioturbation) reworking of the sediment. The adaptation of MOHCB to the redox oscillations was investigated by an experimental ecology approach, subjecting a hydrocarbon-degrading microbial community to contrasting oxygenation regimes including permanent anoxic conditions, anoxic/oxic oscillations and permanent oxic conditions. The most ubiquitous MOHCB, Alcanivorax and Cycloclasticus, showed different behaviours, especially under anoxic/oxic oscillation conditions, which were more favourable for Alcanivorax than for Cycloclasticus. The micro-diversity of 16S rRNA gene transcripts from these genera revealed specific ecotypes for different oxygenation conditions and their dynamics. It is likely that such ecotypes allow the colonization of distinct ecological niches that may explain the success of Alcanivorax and Cycloclasticus in hydrocarbon-contaminated coastal sediments during oil-spills.